Quality of Life Evaluation in Children With Osteogenesis Imperfecta After Giving Bisphosphonate Infusion in Dr. Soetomo Hospital Surabaya - Baskoro Kusumo Riswanto; Sulis Bayusentono (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
INTRODUCTION Osteogenesis imperfecta (OI) or brittle bone disease is a connective tissue formation disorder that is generally characterized by bone fragility, osteopenia, blue sclera, dentinogenesis imperfecta (DI), and hearing loss. Clinical symptoms vary greatly between patients even in the same type. The lack of evaluation of the effect of bisphosphonate on the quality of life of pediatric patients is the main reason for the authors to evaluate the quality of life in pediatric patients with Ostegenesis imperfecta in Soetomo Hospital Surabaya. METHOD The author selected three cases of OI from an outpatient installation of Dr. Soetomo Hospital who was given the management of bisphosphonate administration. Then compared before giving Bisphosphonate and after giving bisphosphonate for 1.5 years and evaluated using the SF36 questionnaire and DASH score. RESULTS In the DASH score assessment, there is no evaluation in the Work Module section (optional) because the patient is still a child. From the results of SF36 evaluation in evaluating the quality of life of patients with Osteogenesis imperfecta in the administration of bisphosphonate, it appears that the development is better compared to before administration of bisphosphonate. DISCUSSION From the evaluation results using the DASH score, all three patients had a good development in terms of motor development in upper extremities. this can be seen from the evaluation of the development of muscle strength and fine motor strength such as writing (drawing), eating his own food without the help of parents and also carrying a heavier burden. It's just that the evaluation of bisphosphonate administration is biased by the motor development of each patient. From the points of Emotional Health and Social Attitude, it can be concluded that patients are bolder to move and move more than before. Before giving bisphosphonate, according to anamnesis from parents, patients are relatively afraid to move, this is due to fear of recurring fractures in patients. After giving bisphosphonate the patient is more willing to move and play with the surrounding environment. From the evaluation of Pain points, there is a significant difference between post and before bisphosphonate administration, this may be due to the reduced frequency of fractures compared to after administration of bisphosphonate. Another important modality in handling OI is rehabilitation of physiotherapy. The goal of rehabilitation in OI patients is primarily to improve joint motion and muscle strength, as well as to improve ambulation and functional ability. OI's condition is chronic and requires lifelong treatment that can reduce children's quality of life. Therefore, in patients with chronic disease conditions that require long-term therapy even for life, it is very important to provide education about understanding children's diseases, the need for lifelong monitoring and treatment, efforts that need to be made to prevent and minimize complications, the importance of the second role parents in providing appropriate parenting, fostering, and fostering for optimal child growth and quality of life CONCLUSION Significant effects were seen after bisphosphonate administration. The need for a thorough evaluation of the effects of bisphosphonate administration on pediatric Osteogenesis Imperfecta patients. The need for a standard and specific questionnaire for the evaluation of the development of bisphosphonate therapy in patients with Osteogenesis Imperfecta.